Rekomendasi Resep Masakan Sehat Berbasis Mobile Untuk Meningkatkan Imunitas Tubuh Selama Pandemi - Nabila Fairuz Zahra; Ratih Kartika Dewi; Issa Arwani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Coinciding with COVID-19 which is designated as a global pandemic by WHO, the Republic of Indonesia Government Regulation Number 21 of 2020 concerning Large-Scale Social Restrictions in the Context of Accelerating the Management of Corona Virus Disease 2019 (COVID-19) is determined by referring to Law Number 6 of 2018 concerning Health Quarantine. To increase the body immunity during a pandemic, one of the attempts is by eating healthy foods with balanced nutrition. Usually, when finding recipes, people often face many choices of recipes, which cause a longer duration of selection to start the cooking process because they will compare one recipe with another. With this application, the user can choose an efficient recipe more quickly. The recommendation system for healthy recipes to increase body immunity during a pandemic was designed using the Simple Additive Weighting (SAW) method. In the use of the SAW method, there were three criteria, namely the number of ingredients, the level of complexity, and calories. The tests carried out were functional testing which is a Blackbox test with 100% valid results, then nonfunctional testing which included comparison testing of system results and manual counting that got 100% results were same and SUS testing with Grade B results on the Grade Scale, Acceptable on Acceptability Ranges, as well as Excellent on Adjective Rating.